P145 'crystalline' clear cases of sarcoidosis?. (December 2018) - De Matteis, S; Cullinan, P
Abstract : Introduction and objectives: Pulmonarysarcoidosis can be clinically, radiologically and histopathologically indistinguishable from silicosis. Misdiagnosis may led to important individual and societal costs, because of the different patient management approaches in terms of treatment and fitness for work. We present a series of silicosis cases previously misdiagnosed as sarcoidosis; we hope to increase awareness among respiratory physicians about the pivotal role of a thorough occupational history in the differential diagnostic process. Method: Between April 2016 and April 2018, 3 men previously diagnosed with pulmonary sarcoidosis were referred to the Occupational Lung Disease service at Royal Brompton Hospital, London, UK to evaluate their fitness for work; all were stonemasons in the UK. A thorough lifetime job history was collected, and combined with the available clinical evidence (i.e. spirometry, radiology, BAL and/or lung biopsy). Results: A summary of the patients is reported in the table 1. In each case, based on the available medical evidence and significant occupational exposures to crystalline silica for over 10 years, a diagnosis of silicosis was reached. Each was advised to avoid further exposure to silica at the workplace, and informed about their eligibility to claim for compensation under the UK Industrial Injuries Disablement Benefit scheme. Of note, cessation of occupational exposure to silica in one of the patients resolved his chronic cough, so that medication was no longer required. Conclusions: Given the chronic nature of silicosis, and the absence of a curative treatment, timely diagnosis is essential to prevent further exposure to the causal agent and so disease progression; to avoid not only unnecessary invasive diagnostic procedures, but also unneeded medications; and to give access to workers' disability compensation.